Dynamics of physical preparedness of runners on middle distances who live in various climatic conditions - Lydmyla Shesterova; Tu Yanhao (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to study the dynamics of physical preparedness of runners on 1500 m who live in various climatic conditions. Material and Methods: 20 qualified runners on middle distances who were divided into two groups took part in the experiment. The first group included 10 runners on 1500 m which are mainly living on the plain, the second - 10 runners on 1500 m which are mainly living in the mountain district. During the research the following methods were used: analysis and synthesis of references, testing, and methods of mathematical statistics. Results: indicators are presented and the analysis of the level of physical preparedness of runners on 1500 m is carried out, living in various climatic conditions in the preparatory and competitive periods of a year macrocycle. Conclusions: it is established that the level of physical preparedness of runners living in various climatic conditions changes not equally during a year macrocycle